Bridging Minds and Vision: The Need for Neurology and Ophthalmology Synergy in Multiple Sclerosis - Chandra, Avinash; Vaidya, Keepa; Rajbhandari, Reema; Shrestha, Tejashwi; Bhandari, Anjali (Nepal Journal of Neuroscience, 2025)
Multiple sclerosis (MS) continues to challenge clinicians and researchers alike with its non-specific and heterogeneous presentation and unpredictable course. Among its earliest and most presenting features is visual dysfunction—commonly optic neuritis—which not only reflects localized optic nerve inflammation but also serves as a harbinger of widespread central nervous system (CNS) pathology. This intimate relationship between vision and neurodegeneration positions the eye as a functional and structural biomarker of MS. Yet, for too long, neurology and ophthalmology have operated in parallel rather than in concert.